1995
DOI: 10.1111/j.1365-2796.1995.tb00899.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary haemostasis in thyroid disease

Abstract: We found that changed primary haemostasis is a general feature of hypothyroidism, and that it is resolved after levothyroxine treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 14 publications
1
45
0
1
Order By: Relevance
“…Hypothyroidism can also lead to abnormal sodium metabolism, increased sympathetic nervous system activity and a decreased glomerular filtration rate, which may contribute to the development of hypertension. [25][26][27] Blood pressure salt sensitivity was also one of the critical factors for hypertension in hypothyroid patients. 28 The study by Gumieniak et al 25 showed that the relationship between free thyroxine index (FTI) and salt sensitivity is partly mediated by the vascular action of the thyroid hormone.…”
Section: Discussionmentioning
confidence: 99%
“…Hypothyroidism can also lead to abnormal sodium metabolism, increased sympathetic nervous system activity and a decreased glomerular filtration rate, which may contribute to the development of hypertension. [25][26][27] Blood pressure salt sensitivity was also one of the critical factors for hypertension in hypothyroid patients. 28 The study by Gumieniak et al 25 showed that the relationship between free thyroxine index (FTI) and salt sensitivity is partly mediated by the vascular action of the thyroid hormone.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative platelet abnormalities have also been reported in patients with hypothyroidism (23)(24)(25). Palareti et al (26) studied 21 patients with acquired hypothyroidism after thyroidectomy, and observed an impaired platelet reactivity not only to ristocetin but also to collagen and adrenalin, which was rapidly normalized after thyroid hormone replacement therapy.…”
Section: Hypothyroidismmentioning
confidence: 94%
“…Myrup et al (23) reported a significant prolongation of bleeding time, an impaired agglutination response to ristocetin, and an increased platelet aggregation in response to ADP in 19 hypothyroid patients as compared to euthyroid controls. Notably, these hemostatic abnormalities normalized after L-thyroxine (L-T 4 ) therapy, suggesting that the prolonged primary hemostasis seen in overt hypothyroidism may be a direct consequence of the hormonal dysfunction (23).…”
Section: Hypothyroidismmentioning
confidence: 99%
“…Most abnormalities have been attributed to decreased synthesis or activity of clotting factors, including von Willebrand factor (VWF) and factor VIII (FVIII:C), or to decreased response to adrenergic stimulation (enhanced VWF release from endothelial cells) due to thyroid hormone deficiency (1,6,7). Other authors have suggested that autoimmunity may be involved (20,21).…”
Section: Introductionmentioning
confidence: 99%